Hollies at a Glance - Sydney Park Brown; Dewayne L. Ingram; William E. Barrick (EDIS, 2012)
Hollies are reliable, low-maintenance plants for Florida landscapes. Diverse sizes, forms, and textures exist, ranging from large trees to dwarf shrubs. Some hollies can be used as informal or formal hedges or as foundation plants, while others make beautiful accent or specimen plants. Many are valued for their colorful berries, which provide food for birds and brighten the fall and winter seasons. Several hollies are native to Florida. This revised 5-page fact sheet includes a list of dozens of popular hollies sold in Florida. Written by Sydney Park Brown, Dewayne L. Ingram, and William E. Barrick, and published by the UF Department of Environmental Horticulture, March 2012.